A Quick reCAP: Discovering Cryptococcus neoformans Capsule Mutants - Daphne Boodwa-Ko; Tamara L. Doering (Journal of Fungi, 2024)
Cryptococcus neoformans is an opportunistic fungal pathogen that can cause severe meningoencephalitis in immunocompromised hosts and is a leading cause of death in HIV/AIDS patients. This pathogenic yeast is surrounded by a polysaccharide capsule that is critical for virulence and plays important roles in host-pathogen interactions. Understanding capsule biosynthesis is therefore key to defining the biology of C. neoformans and potentially discovering novel therapeutic targets. By exploiting methods to identify mutants deficient in capsule, June Kwon-Chung and other investigators have discovered numerous genes involved in capsule biosynthesis and regulation. Successful approaches have incorporated combinations of techniques including mutagenesis and systematic gene deletion; complementation and genetic screens; morphological examination, physical separation, and antibody binding; and computational modeling based on gene expression analysis. In this review, we discuss these methods and how they have been used to identify capsule mutants.